KETUHANAN YANG MAHA ESA MENURUT BUYA HAMKA STUDI TAFSIR AL-AZHAR - Mandra Jaya; Risan Rusli (STAI Asy-Syukriyyah, 2023)
: This article examines Buya Hamka's interpretation of Al-Azhar's Interpretation of Belief in the One and Only God. This study is part of a literature study that collects data from various literatures. Apart from books, research literature can also be in the form of magazines, journals, and other types of documentation. By looking for data about Belief in the One and Only God According to Buya Hamka in Tafsir Al-Azhar. A variety of relevant literature Research results According to Buya Hamka, the main center of Pancasila lies in the stipulations of Belief in One Almighty God. Buya Hamka emphasized that by adhering to the provisions of Belief in the One and Only God, he would usually develop and practice the other four provisions. In the book of Interpretation of Al-Azhar letter Al-Ikhlas mentions: 1.QS. Al-Baqarah:163